Behavioral influences on strategic interactions outcomes in game theory models - Kuzmanović, Marija (Yugoslav Journal of Operations Research, 2021)
Traditional decision-making models assume full rationality of all actors. Nevertheless, the practice has shown that the behavior and choices of actors are influenced by many factors such as motives, beliefs, opinions, personal and social preferences, as well as cognitive biases. Moreover, it has already been proven that people have limitations in their ability to collect relevant information and respond to them, i.e., they are bounded rational. All this has contributed to the development of behavioral models in many disciplines including game theory. This paper provides a detailed review of the literature regarding behavioral models of strategic decision making. Bounded rationality and other cognitive biases in the strategic interactions are illustrated through the findings of numerous experimental studies.